Immobilization of Aspergillus Oryzae ?-Galactosidase in an Agarose Matrix Functionalized by Four Different Methods and Application to the Synthesis of Lactulose - Vera-Vera, C (Elsevier Ltd, 2017)
Aspergillus oryzae β-galactosidase was immobilized in monofunctional glyoxyl-agarose and heterofunctional supports (amino-glyoxyl, carboxy-glyoxyl and chelate-glyoxyl agarose), for obtaining highly active and stable catalysts for lactulose synthesis. Specific activities of the amino-glyoxyl agarose, carboxy-glyoxyl agarose and chelate-glyoxyl agarose derivatives were 3676, 430 and 454 IU/g biocatalyst with half-life values at 50 °C of 247, 100 and 100 h respectively. Specific activities of 3490, 2559 and 1060 IU/g were obtained for fine, standard and macro agarose respectively. High immobilization yield (39.4%) and specific activity of 7700 IU/g was obtained with amino-glyoxyl-agarose as support. The highest yields of lactulose synthesis were obtained with monofunctional glyoxyl-agarose. Selectivity of lactulose synthesis was influenced by the support functionalization: glyoxyl-agarose and amino-glyoxyl-agarose derivatives retained the selectivity of the free enzyme, while selectivity with the carboxy-glyoxyl-agarose and chelate-glyoxyl-agarose derivatives was reduced, favoring the synthesis of transgalactosylated oligosaccharides over lactulose. © 2017 Elsevier Ltd